Teaching Values through Literature and Advancing SDG 4: A UNESCO-Based Analysis of Peace, Justice, and Equality in English Literary Works - Masulah Masulah; Fabiola Dharmawanti Kurnia; Ali Mustofa (Journal of Current Studies in SDGs, 2026)
Objective: Investigating the representation of UNESCO core values in selected literary works taught in an English Literature program and explores their contribution to values-based education. Method: The research employed a qualitative case study approach. Data were collected through textual analysis of selected literary works, including Julius Caesar, Othello, King Lear, Oedipus, Goblin Market, and When I Was One-and-Twenty. The data were interpreted using UNESCO’s framework of core human values. Results: The findings reveal that the selected literary works prominently represent the values of peace, justice, and equality. These values are reflected through characters’ moral struggles, ethical decisions, social relationships, and responses to power, prejudice, and responsibility. The analysis shows that literary texts provide meaningful opportunities for students to engage critically with social and moral issues while developing empathy, ethical awareness, and respect for diversity. Novelty: Providing a novel contribution by examining how English literary works function as pedagogical resources for integrating UNESCO core values particularly peace, justice, and equality into literature teaching in higher education. It demonstrates that literary narratives not only enhance students’ literary competence but also foster character development, ethical awareness, and values-based learning. Furthermore, the study extends the discourse on literature education by highlighting its contribution to Sustainable Development Goal 4 (Quality Education), particularly Target 4.7, through promoting global citizenship, respect for human rights, cultural diversity, and a culture of peace.